Evaluation of Traps and Profenofos Insecticide for Controlling Fruit Fly (Bactrocera spp.) on Chili Pepper (Capsicum frutescens L.) - Muhammad Botek; Gusnawaty HS; Muhammad Taufik; Rahayu M; Nur Isnaini Ulfa; Irwanto (JURNAL AGRIMENT, 2026)
ABSTRACT Chili pepper (Capsicum frutescens L.) is a commodity with numerous benefits and high economic value. One of the major pests causing yield losses in chili pepper cultivation is the fruit fly (Bactrocera spp.). Its control can be achieved through an integrated pest management approach utilizing traps, pheromones, and insecticides. This study aimed to determine the effect of two types of traps and the insecticide profenofos on the intensity of fruit fly (Bactrocera spp.) infestation in chili pepper plants. The study employed a randomized block design (RBD) consisting of four treatments: control (A0), yellow traps (A1), petrogenol-based traps (A2), and the chemical insecticide profenofos (A3). The observed variables included fruit fly infestation intensity, number of fruits, and fruit weight. Data were analyzed using analysis of variance (ANOVA), followed by an Honestly Significant Difference (HSD) test at a 95% confidence level. Petrogenol-based traps were effective in controlling fruit fly (Bactrocera spp.) infestation in chili pepper (C. frutescens L.) plants, with an infestation intensity of 1,83%, producing up to 162,80 fruits and a fruit weight of 34,34 g.